Thoracic Ectopia Cordis - Muktan, Dipak; Singh, Rupa R; Bhatta, Nisha Keshary (Journal of Nepal Paediatric Society, 2018)
Ectopia Cordis is a rare congenital anomaly characterized by partial or complete displacement of the heart outside the thoracic cavity with an estimated incidence of 5 to 8 per million live births We report a case of a 22-year-old primigravida, unbooked and immunized woman, with no relevant family or personal history, in which the prenatal fetal ultrasound, performed at 34 weeks of gestation, revealed a defect of the anterior chest wall with exteriorization of the heart. Baby was Pre-term 34 week by date but term by modified Ballard scoring, male weighing 2.4 kg delivered by lower segment caesarean section. Baby had complete thoracic ectopia cordis with large defect in anterior wall of chest and sternum was absent.